2017
DOI: 10.1007/s00018-017-2726-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-shed vesicles from the parasite Trichomonas vaginalis: characterization and their association with cell interaction

Abstract: Trichomonas vaginalis is a common sexually transmitted parasite that colonizes the human urogenital tract, where it remains extracellular and adheres to epithelial cells. Infections range from asymptomatic to highly inflammatory, depending on the host and the parasite strain. Despite the serious consequences associated with trichomoniasis disease, little is known about parasite or host factors involved in attachment of the parasite-to-host epithelial cells. Here, we report the identification of microvesicle-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 61 publications
3
68
0
Order By: Relevance
“…Briefly, sEV preparations were diluted 1000× and 50,000× in PBS and quantified using the ZetaView ® (Particle Metrix, Meerbusch, Germany) by translational diffusion size distribution. Nanotracking analysis confirmed presence of sEVs from TV cultures in the peak size range of 76.6-106.9 nm similar to those previously reported for T. vaginalis (Twu et al, 2013;Olmos-Ortiz et al, 2017;Nievas et al, 2018) and at peak concentrations ranging from 1.1E9-1.65E11 particles/ml (Supplementary Figure S2A). Transmission electron microscopy with immunogold labelling of CD63 confirmed the presence of exosomes in the sEV samples (Supplementary Figure S2B).…”
Section: Isolation Of Small Extracellular Vesiclessupporting
confidence: 86%
“…Briefly, sEV preparations were diluted 1000× and 50,000× in PBS and quantified using the ZetaView ® (Particle Metrix, Meerbusch, Germany) by translational diffusion size distribution. Nanotracking analysis confirmed presence of sEVs from TV cultures in the peak size range of 76.6-106.9 nm similar to those previously reported for T. vaginalis (Twu et al, 2013;Olmos-Ortiz et al, 2017;Nievas et al, 2018) and at peak concentrations ranging from 1.1E9-1.65E11 particles/ml (Supplementary Figure S2A). Transmission electron microscopy with immunogold labelling of CD63 confirmed the presence of exosomes in the sEV samples (Supplementary Figure S2B).…”
Section: Isolation Of Small Extracellular Vesiclessupporting
confidence: 86%
“…Attachment of one trichomonad is shown to facilitate the enrolment of others, through the secretion of chemo-attractant [136]. A recent study reported the release of membrane vesicles from T. vaginalis surface that interact with target host cells through receptor or through fusion with target cell membrane to deliver certain signals important for this parasite pathogenesis [137].…”
Section: Trichomoniasis/trichomonas Vaginitis (Tv) Initiation Of Pathmentioning
confidence: 99%
“…Proteomic analysis of exosomes and ectosomes revealed large numbers of proteins as their possible cargoes (215 and 592, respectively), including three paralogs of α‐SCS in exosomes and four paralogs of hydrogenosomal malic enzyme in ectosomes (Nievas et al. ; Twu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) T. vaginalis has been reported to release microvesicles that are derived from endocytic compartments (exosomes) or the plasma membrane (ectosomes). Proteomic analysis of exosomes and ectosomes revealed large numbers of proteins as their possible cargoes (215 and 592, respectively), including three paralogs of a-SCS in exosomes and four paralogs of hydrogenosomal malic enzyme in ectosomes (Nievas et al 2018;Twu et al 2013). These findings provide new potential modes of protein export and delivery to target cells; however, whether the two hydrogenosomal proteins represent specific cargoes in microvesicles needs to be experimentally verified.…”
Section: Figurementioning
confidence: 99%